Significance of Buddhist Perspectives in Natural Resource Management (Scientific Researches in Academia, 2024)
Eco-spirituality in Buddhism provides significant insights and practical advice for dealing with modern environmental concerns and reaching long-term ecological balance. The Buddhist perspectives in Natural Resource Management not only address ecological issues but also encourage long-term environmental stewardship and balance, providing a meaningful and ethical framework for natural resource management. Buddhist concepts like mindfulness, compassion, and nonviolence promote ethical and sustainable connections with nature. By perceiving the environment as a sacred thing, eco-spirituality promotes behaviors that safeguard and maintain natural resources in ethical ways. Natural Resource Management aligns with Buddhist teachings, focusing on material and spiritual well-being. Buddha's teachings serve as a tool for enlightenment and promoting harmony between humans and the environment. It interconnects all life forms and the importance of resources. In this view, the purpose of this paper is to highlight the significance of Buddhist perspectives on natural resource management including consequences such as conservation measures and efficient resource use, which are critical to sustaining ecological equilibrium.